Odontogenic Descending Necrotizing Mediastinitis in a Patient with Severe Allergy to Beta-Lactam Antibiotics: A Case Report and Literature Review - Ayşe BATIREL; Ferhat ARSLAN; Serdar ÖZER; Hatice ERYİĞİT; Recep DEMİRHAN; Sedef BAŞGÖNÜL (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2013)
Descending necrotizing mediastinitis (DNM) is caused by aerobic and anaerobic bacteria as a rare but severe complication of oropharyngeal abscesses developing secondary to odontogenic infections. Patients with hypersensitivity reaction to beta-lactam antibiotics pose challenges in the treatment. To our knowledge, only two cases of postoperative mediastinitis treated with tigecycline have been reported in the English medical literature to date. In this paper, we present a case of descending mediastinitis developing one week after dental extraction. The patient was given tigecycline treatment with the diagnosis of complicated deep neck infection, which progressed to descending mediastinitis because of severe allergic reaction to beta-lactam group antimicrobials. He successfully recovered after early surgical drainage and debridement together with four weeks of tigecycline therapy. Tigecycline may be an alternative option for treatment of odontogenic infections and descending mediastinitis in beta-lactamallergic patients. It may be used effectively and successfully with concurrent standard early surgical intervention in selected patients, especially in those with severe hypersensitivity reaction.